A eficácia da intervenção terapêutica fonoaudiológica nos Distúrbios do Espectro Autístico - Tamanaha, Ana Carina [UNIFESP] (2008)
Purpose: Evaluate the efficacy of the speech and language therapy for Autistic Spectrum Disorders. Methods: The design of this study is the Clinical Trial. The sample was composed of 11 children diagnosed with Autism (6) and Asperger Syndrome (5) attended in the Language and Speech Laboratory – Autistic Spectrum Disorders at Federal University of São Paulo. These children were randomly divided into two groups: Six were receiving both direct and indirect intervention (Therapy Group-TG), and five were receiving exclusively indirect intervention (Orientation Group-OG). We used the following parts of ASIEP-2 (Krug et al, 1993): Autism Behavior Checklist (ABC), Interaction Assessment (IA) and Sample of Vocal Behavior (SVB) on three occasions: at the beginning, six months later and 12 months later. Results: We observed there was greater evolution of Therapy Group –TG in the Autism Behavior Checklist, Interaction Assessment and Sample of Vocal Behavior. The mothers and the Speech and Language Therapist perceived behavioral changes. The influence of the multidisciplinary diagnosis, age and measures of the adaptive functioning was analysed. The performance of children with Asperger Syndrome was considered more positive. There was greater evolution in the children with age 73 month or more, and in the children with normal, mild and moderate adaptive functioning. Conclusions: The tendency of better performance of the children attended in direct and indirect intervention showed that this association was fundamental.